Desenvolvimento vegetativo, características anatômicas e fitoquímicas de plantas jovens de duas espécies de guaco, submetidas a diferentes condições de qualidade de radiação - Souza, Girlene Santos de (2006)
Guaco (Mikania laevigata and Mikania glomerta) Asteraceae is a plant of recognized medicinal importance due to the production of cumarine a substance that among several properties, it has anti-inflamatory, bronchium dilatardora, anti cancerigena action. Environmental factors that interfere on the cropping conditions of medicinal species, such as the solar radiation quality, alter morphological plant characteristics and consequently the syntheses of secondary compounds. This study evaluated the effect of the light on vegetative development, anatomic alterations and phytochemistry characteristics of guaco, shaded by colored net (blue, red and gray) and plants fully exposed to the sun light. The plants shaded by blue net produced more total dry matter and foliar area as compared to the plants shaded by red or gray nets and plants fully exposed to the sun Plants grown under fully exposed plants had different root/shoot, a/b chlorophyll and foliar area/foliar weight ratios as compared with plants growing under shaded conditions. Anatomic characteristics of the Guaco species were altered by colored net. For both Guaco species, plants growing under blue net produced more essential oils than plants growing on the other tested conditions. Regardless of the treatment, M. gloemrata had greater cumarina content than M. laevigata.